Role Effectiveness of KPPU Regional Office I Medan in Supervising Partnerships - Nurasiah Harahap (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2022)
The legal arrangement of the Business Competition and Partnership Supervisory Commission has accommodated the needs of large business actors and UMKM in improving the economy of the Indonesian people through the implementation of partnership agreements between large business actors and small business actors properly, the KPPU Regional Office I Medan is authorized to carry out supervision. The role of the KPPU's Regional Office I Medan from 2015-2019 there was 1 case of partnership in the core-plasma pattern of oil palm plantations that had been handled by the KPPU's Regional I Medan Office, the handling was stopped for further advocacy. And since 2020 until now received 5 reports of which 1 partnership pattern and 4 forms of core-plasma partnership in oil palm plantations and conducted research case initiatives totaling 2 studies with core-plasma partnership pattern and followed up with advocacy. The handling carried out by the KPPU Regional Office I Medan has followed the procedures of the central office. However, the role of the KPPU in the Medan Region I office has not been effective. The application of sanctions to business actors is carried out by the commission assembly in the form of administrative sanctions and the KPPU Regional Office I Medan has never recommended revoking a business license nor has it been declared a violation of the recommendation. This reality is inseparable from the existence of obstacles in the implementation of the KPPU's Regional Office I in supervising partnerships, both internal constraints, related to distance, costs, human resources, technology, and time, as well as external constraints related to awareness of the legal culture of business actors. Finally, it is hoped that the government should increase the costs for carrying out the commission's duties to play an effective role and provide education to business actors in understanding partnership agreements.